Effects of cytokinin on multiple shoot formation from shoot tips of cabbage (brass/ca oleracea subsp. capitata cv. tropicana.) - Tengku Mustafa Kamal, Tengku Laila Kamaliah; Abdul Rashid, Azmi; Abdul Aziz, Maheran; Hassan, Siti Aishah (2001)
Conditions for plant regeneration from excised shoot tips of Brassica oleracea subsp. capitata were studied. The aim of this study was to determine suitable concentration of cytokinin for multiple shoot formation. Seven days old shoot tips were excised from in vitro-grown seedlings and cultured on MS medium containing }/-benzyladenine (BA) at 3, 6, 9, 12, 15 and 18 mg/l (13.3, 26.6, 39.9, 53.2, 66.5 and 79.8 uM) or 6-furfuryl aminopurine (kinetin) at 6, 12, 18, 24, 30 and 36 mg/l (27.8, 55.6,83.4, 111.2, 139 and 166.8 uM). The addition of cytokinin induced a variable amount of callus at the base of the shoot tip, followed by multiple shoot formation. The highest mean number of transferable shoots per ex plant and the highest percentage of shoot formation were produced on 3 and 6 mgBA per liter (13.3 and 26.6 uM) respectively. On kinetin-containing media, the highest mean number of transferable shoots per ex plant and the highest percentage of shoot formation were attained on 6 mg/l kinetin. Multiple shoots were formed within 4 weeks. Regenerated shoots were rooted on hormone free MS medium.